2016
DOI: 10.20546/ijcmas.2016.512.090
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Zinc Oxide Nanoparticles and Curcumin in Amelioration the Toxic Effects in Aflatoxicated Rabbits

Abstract: As the first step in this direction; biosynthesis and characterization of zinc oxide nanoparticles (ZnO-NPs) and their use to ameliorate the toxic effects of aflatoxicosis in rabbit in comparison with curcumin were studied. Thirty-five healthy New Zealand rabbits were divided into 5 groups, each including 7 rabbits. Group 1 was kept as negative control without any treatment. Rabbits in the groups 2, 3, 4 and 5 were given AFB 1 orally at a dose of 50 ug dissolved in 0.5 ml of olive oil/ animal daily, for 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…Zinc was found to ameliorate oxidative stress and glutathione depletion and involved in all processes concerned with cell protection through activation of DNA repair, thus preventing apoptosis and cell proliferation [71]. ZnO NPs act as an effective adjuvant treatment to chemotherapeutic drugs that may cause male reproductive dysfunction [31] and as a hepatic cytoprotective agent against Aflatoxin B1 exposure, when used in low doses, by improving the antioxidant activity, and decreasing the free radicals level [72]. Studies also showed suppressed MDA content by ZnO NPs treatment in a dose-dependent manner, thus reducing oxidative stress [69,35], therefore, protecting cell membrane integrity against oxidative stress damage, and increasing antioxidant enzyme levels [73].…”
Section: Results Of the Present Study Indicated That Zno Nps Treatmementioning
confidence: 99%
“…Zinc was found to ameliorate oxidative stress and glutathione depletion and involved in all processes concerned with cell protection through activation of DNA repair, thus preventing apoptosis and cell proliferation [71]. ZnO NPs act as an effective adjuvant treatment to chemotherapeutic drugs that may cause male reproductive dysfunction [31] and as a hepatic cytoprotective agent against Aflatoxin B1 exposure, when used in low doses, by improving the antioxidant activity, and decreasing the free radicals level [72]. Studies also showed suppressed MDA content by ZnO NPs treatment in a dose-dependent manner, thus reducing oxidative stress [69,35], therefore, protecting cell membrane integrity against oxidative stress damage, and increasing antioxidant enzyme levels [73].…”
Section: Results Of the Present Study Indicated That Zno Nps Treatmementioning
confidence: 99%
“…Moreover, ZnO NPs at low doses have a hepatoprotective effect through the scavenging of free radicals or promotion of antioxidant activities, which detoxify the free radicals. 62 Doxorubicin produces its antitumor effects and toxicity by the formation of intracellular ROS and free radicals which intercalated with DNA and led to subsequent inhibition of topoisomerase. 63 Regarding doxorubicin-induced genotoxicity, the results from the G3 group showed a significant (P ≤ 0.05) increase in DNA-damaging parameters (tail length, DNA tail percentage and tail moment) in sperm cells compared with the control (G1).…”
Section: Discussionmentioning
confidence: 99%
“…A study reported the ameliorative effect of co-administered curcumin and ZnO NPs to the hepatotoxicity caused by aflatoxin B1 (AFB1) on AFB1-fed rabbits. ZnO and curcumin demonstrated hepatoprotective effect through scavenging free radicals and by enhancing the activities of antioxidants superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) [ 56 ].…”
Section: Metal Oxides As Curcumin Carriersmentioning
confidence: 99%